How and why to monitor Pseudomonas aeruginosa infections in the long term at a cystic fibrosis centre - Kalferstova, L; Vilimovska Dedeckova, K; Antuskova, M; Melter, O; Drevinek, P (The Journal of hospital infection, 2016)
BACKGROUND: Pseudomonas aeruginosa is a major cystic fibrosis (CF) pathogen causing chronic respiratory infections and posing a risk for cross-infection between patients with CF. AIM: To propose an algorithm for long-term surveillance of P. aeruginosa and assess its suitability for monitoring the epidemiological situation at a CF centre with approximately 300 patients. METHODS: Over a nine-year period, over 300 P. aeruginosa isolates from 131 infected patients were tested by multi-locus sequence typing (MLST) and/or random amplified polymorphic DNA (RAPD) assay. FINDINGS: MLST analysis led to the identification of 97 different sequence types which were distributed among 17 RAPD-generated (pseudo)clusters. This indicates that the easy-to-perform RAPD assay is only suitable for intra-individual, not interindividual, strain analyses. No epidemic strains were observed. Longitudinal analysis revealed that 110 of the 131 patients were infected with the same strain over the observation period, whereas 21 patients had a strain replacement or a new infection. Chronic infection was found in 99 of the 131 patients, and the remaining 32 patients met the criteria for intermittent infection (as defined by the Leeds criteria). Eighteen of the 32 patients (56%) with intermittent infection were infected with the same strain for up to nine years. CONCLUSION: The strain type only changed in 16% of 131 patients with chronic or intermittent infection. As many as 56% of patients considered to have intermittent infection were actually chronically infected with the same strain for many years.
Keywords: Chronic infection; senioři; Pseudomonas Infections; longitudinální studie; molekulární epidemiologie; senioři nad 80 let; genotyp; Genotype; MLST; Middle Aged; RAPD; technika náhodné amplifikace polymorfní DNA; Adult; mladý dospělý; Cross Infection; Cystic fibrosis; dítě; Cystic Fibrosis; Child; Aged, 80 and over; Child, Preschool; Multilocus Sequence Typing; Young Adult; Pseudomonas aeruginosa; ženské pohlaví; Humans; předškolní dítě; Random Amplified Polymorphic DNA Technique; Molecular Epidemiology; epidemiologické monitorování; pseudomonádové infekce; lidé středního věku; Surveillance; infekce spojené se zdravotní péčí; Longitudinal Studies; dospělí; multilokusová sekvenční typizace; Epidemiological Monitoring; Aged; Female; Intermittent infection; lidé; cystická fibróza